A conductive masterbatch based on carbon nanotubes and preparation method thereof

By preparing isocyanate-based doped carbon nanotubes and mixing them with other materials, the conductive masterbatches are prepared, which solves the problem of uneven conductivity and significantly improves the conductivity and mechanical properties of polymer materials.

CN118459884BActive Publication Date: 2025-02-14JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410446927.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-15
Publication Date
2025-02-14
Estimated Expiration
2044-04-15

AI Technical Summary

Technical Problem

After the existing conductive masterbatches are added to polymer materials, the carbon nanotubes cannot be effectively dispersed, resulting in uneven conductivity, the volume resistivity cannot be effectively reduced, and the conductive performance improvement effect is poor.

Method used

Conductive masterbatches are prepared by preparing isocyanate-doped carbon nanotubes and mixing them with polymer powder, oxidized polyethylene wax, polyvinylpyrrolidone, antioxidant and stearic acid, and then preparing conductive masterbatches by extrusion granulation to achieve Uniform dispersion and efficient conduction of carbon nanotubes.

Benefits of technology

It significantly improves the conductivity of polymer materials, enhances the conductivity and mechanical properties of carbon nanotubes, avoids interface slips, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118459884B_ABST
    Figure CN118459884B_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymer materials, and in particular to a conductive masterbatch based on carbon nanotubes and a preparation method thereof, which are used to solve the problem that after the existing conductive masterbatch is added with the polymer material, the volume resistivity of the polymer material cannot be effectively reduced and the conductive performance improvement effect is poor; the conductive masterbatch comprises polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, an antioxidant and stearic acid; the carbon nanotubes in the conductive masterbatch have high conductive performance and excellent mechanical properties, and the conductive masterbatch prepared from the conductive masterbatch can have excellent conductivity, and the doping of metal oxides can effectively enhance the effective transfer of electrons and stress between adjacent carbon nanotubes, further improving the conductivity of the carbon nanotubes, and then the surface of the doped carbon nanotubes is modified with organic matter, so that the dispersibility of the doped carbon nanotubes in the polymer carrier is significantly improved, thereby achieving the best conductivity enhancement effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a conductive masterbatch based on carbon nanotubes and a preparation method thereof. Background Art

[0002] With the continuous development of science and technology, polymer materials are increasingly used in various fields, and are widely used in electronic products, auto parts, medical equipment, chemical containers, pipelines and other products. However, the volume resistivity of polymer materials is relatively high, which makes it easy for static electricity to accumulate on the surface of polymer products. Static electricity will have many adverse effects after accumulating on polymer products. Static electricity adsorbs dust and not only affects the appearance of the product, especially for electronic products, but also affects its performance, and even causes discharge, which can cause fire and explosion accidents in special occasions. Therefore, it is very necessary to remove static electricity in polymer materials.

[0003] At present, a common method is to add conductive masterbatch of carbon nanotubes to polymer materials. However, after the existing conductive masterbatch is added to the polymer material, the carbon nanotubes cannot be effectively dispersed into the polymer material, which often leads to uneven conductive properties, resulting in the inability to effectively reduce the volume resistivity of the polymer material and poor improvement of the conductive properties, which limits its application in conductive polymer composite materials. Summary of the invention

[0004] In order to overcome the above technical problems, the purpose of the present invention is to provide a conductive masterbatch based on carbon nanotubes and a preparation method thereof, which solves the problem that after the existing conductive masterbatch is added to the polymer material, the volume resistivity of the polymer material cannot be effectively reduced and the conductive performance improvement effect is poor.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A conductive masterbatch based on carbon nanotubes, comprising the following components in parts by weight:

[0007] 60-80 parts of polymer powder, 8-22 parts of isocyanate-doped carbon nanotubes, 5-13 parts of oxidized polyethylene wax, 5-13 parts of polyvinyl pyrrolidone, 1.5-3.5 parts of antioxidant and 1-3 parts of stearic acid;

[0008] Wherein, the isocyanate-doped carbon nanotubes are prepared by the following steps:

[0009] Step s1: Add carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid into a three-necked flask equipped with a stirrer and a thermometer, perform ultrasonic dispersion for 30-40 minutes at a temperature of 25-30°C and an ultrasonic frequency of 40-50kHz, then stir and react for 3-5 hours at a temperature of 85-90°C and a stirring rate of 400-450r / min. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with distilled water until it is neutral, then place it in a vacuum drying oven, and dry it at a temperature of 80-85°C for 2-3 hours to obtain acidified carbon nanotubes;

[0010] Step s2: adding polyvinyl pyrrolidone and anhydrous methanol to a three-necked flask equipped with a stirrer and a thermometer, stirring the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 400-450r / min, then adding acidified carbon nanotubes and continuing to stir the reaction for 20-30 minutes, then adding cadmium acetate solution and continuing to stir the reaction for 1-1.5 hours, after the reaction is completed, adjusting the pH of the reaction product to 8-9 with sodium hydroxide solution, then vacuum filtering, washing the filter cake with distilled water for 3-5 times, then placing it in a vacuum drying oven, drying it at a temperature of 130-140°C for 2-3 hours, then placing it in a muffle furnace, calcining it at a temperature of 280-300°C for 3-4 hours, and then cooling it with the furnace to obtain doped carbon nanotubes;

[0011] Step s3: adding doped carbon nanotubes and thionyl chloride into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stirring the reaction for 15-20 minutes at a temperature of 25-30°C and a stirring rate of 400-450r / min, then heating to reflux and continuing stirring the reaction for 2-3 hours, after the reaction is completed, vacuum filtering the reaction product, washing the filter cake with distilled water for 3-5 times, and then placing it in a vacuum drying oven and drying it at a temperature of 50-60°C for 2-3 hours to obtain chlorinated carbon nanotubes;

[0012] Step s4: adding acyl chloride carbon nanotubes and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersing them for 30-40 minutes at a temperature of 25-30°C and an ultrasonic frequency of 40-50kHz, then adding tetraethylenepentamine and continuing ultrasonically dispersing for 10-15 minutes, and then stirring the reaction for 8-10 hours at a temperature of 85-90°C and a stirring rate of 400-450r / min under nitrogen protection, and after the reaction is completed, cooling the reaction product to room temperature, and then vacuum filtering, washing the filter cake with distilled water for 3-5 times, and then placing it in a vacuum drying oven, and drying it for 3-4 hours at a temperature of 60-70°C to obtain polyamino carbon nanotubes;

[0013] Step s5: Add polyamino carbon nanotubes and anhydrous toluene into a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically disperse them for 30-40 minutes at a temperature of 25-30°C and an ultrasonic frequency of 40-50kHz, then add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate and continue ultrasonically dispersing for 10-15 minutes, and then stir the reaction at a temperature of 60-65°C, a stirring rate of 400-450r / min, and nitrogen protection for 8-10 hours. After the reaction, cool the reaction product to room temperature, and then vacuum filter it. Wash the filter cake with distilled water for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 45-50°C for 10-15 hours to obtain isocyanate-doped carbon nanotubes.

[0014] As a further solution of the present invention: the usage ratio of the carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step s1 is 5g:90-120mL:30-40mL.

[0015] As a further solution of the present invention: the carbon nanotubes in step s1 are multi-walled carbon nanotubes with an outer diameter range of 40-60 nm and a length of 5-10 μm; the mass fraction of the concentrated sulfuric acid is 95-98%, and the mass fraction of the concentrated nitric acid is 68%.

[0016] As a further solution of the present invention: the dosage ratio of the polyvinyl pyrrolidone, anhydrous methanol, acidified carbon nanotubes and cadmium acetate solution in step s2 is 0.8-1g:100-120mL:1g:50-60mL.

[0017] As a further solution of the present invention: the molar concentration of the cadmium acetate solution in step s2 is 0.3-0.5 mol / L; the mass fraction of the sodium hydroxide solution is 15-20%.

[0018] As a further solution of the present invention: the usage ratio of the doped carbon nanotubes and dithionyl chloride in step s3 is 1 g: 35-40 mL.

[0019] As a further solution of the present invention: the usage ratio of the chlorinated carbon nanotubes, N,N-dimethylformamide and tetraethylenepentamine in step s4 is 2g:40-45mL:0.5-2.5g.

[0020] As a further solution of the present invention: the usage ratio of the polyamino carbon nanotubes, anhydrous toluene, 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate in step s5 is 2g:120-130mL:3-6g:0.3-0.7g.

[0021] As a further solution of the present invention: a method for preparing a conductive masterbatch based on carbon nanotubes, comprising the following steps:

[0022] Step 1: Weigh 60-80 parts of polymer powder, 8-22 parts of isocyanate-doped carbon nanotubes, 5-13 parts of oxidized polyethylene wax, 5-13 parts of polyvinyl pyrrolidone, 1.5-3.5 parts of antioxidant and 1-3 parts of stearic acid according to weight parts, and set aside;

[0023] Step 2: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes.

[0024] As a further solution of the present invention: the polymer powder is one of polyethylene powder, polypropylene powder, chlorinated polypropylene powder, polystyrene powder and polyamide 6 powder; the antioxidant is one of antioxidant 1010, antioxidant 168 and antioxidant 1076.

[0025] Beneficial effects of the present invention:

[0026] The present invention discloses a conductive masterbatch based on carbon nanotubes and a preparation method thereof. The carbon nanotubes are treated with concentrated sulfuric acid and concentrated nitric acid to acidify the carbon nanotubes, thereby introducing a large number of carboxyl groups on the surface of the carbon nanotubes, increasing the types and quantities of surface functional groups, and obtaining acidified carbon nanotubes. The acidified carbon nanotubes are then treated with cadmium acetate solution and sodium hydroxide solution to dope metal oxides in the inner cavity and on the surface of the acidified carbon nanotubes to obtain doped carbon nanotubes. The doped carbon nanotubes are then treated with thionyl chloride to convert the carboxyl groups on the doped carbon nanotubes into acyl chloride groups, further increasing the reaction activity, and obtaining acyl chloride carbon nanotubes. tubes, then using chlorinated carbon nanotubes and tetraethylenepentamine to react, the acyl chloride groups on the chlorinated carbon nanotubes react with the amino groups on the tetraethylenepentamine, thereby introducing a large number of amino groups and secondary amine groups to obtain polyamino carbon nanotubes, then the amino groups and secondary amine groups on the polyamino carbon nanotubes react with the isocyanate groups on 4,4'-diphenylmethane diisocyanate, and simultaneously introducing a large number of isocyanate groups to obtain isocyanate-doped carbon nanotubes, and finally the isocyanate-doped carbon nanotubes, polymer powder, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid are mixed and extruded into granules to obtain a conductive masterbatch based on carbon nanotubes;

[0027] The carbon nanotubes in the conductive masterbatch based on carbon nanotubes have high conductivity and excellent mechanical properties. The conductive masterbatch made of the carbon nanotubes can have excellent conductivity. When metal oxides are doped thereon, the metal oxides form "welding points" at the intersections of the carbon nanotubes to play a welding role, so as to ensure that the carbon nanotubes can overlap each other and form an overall conductive path in the polymer. The metal oxides can also fill the inner cavity of the carbon nanotubes. Therefore, the doping of metal oxides can effectively enhance the effective transfer of electrons and stresses between adjacent carbon nanotubes, and at the same time avoid the interface slip of the carbon nanotubes during the cyclic stretching and release process, thereby further improving the conductivity of the carbon nanotubes. After that, the surface of the doped carbon nanotubes is modified with organic matter, so that the organic matter is grafted to wrap it, so that the dispersibility of the doped carbon nanotubes in the polymer carrier is significantly improved, thereby achieving the best conductivity enhancement effect, and the large number of isocyanate groups introduced can be chemically bonded to the base material that needs to be modified for conductivity, thereby further enhancing its mechanical properties, making full use of its enhancement effect, and significantly improving the conductivity of the base material.

[0028] The present invention will be further described below in conjunction with the accompanying drawings.

[0029] Figure 1 The present invention is a flow chart of a method for preparing a conductive masterbatch based on carbon nanotubes. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0031] See also Figure 1 As shown, this embodiment is a method for preparing a conductive masterbatch based on carbon nanotubes, comprising the following steps:

[0032] Step S1: 5 g of carbon nanotubes, 90 mL of concentrated sulfuric acid with a mass fraction of 95%, and 30 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 30 min at a temperature of 25° C. and an ultrasonic frequency of 40 kHz, and then stirred for reaction for 3 h at a temperature of 85° C. and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filter cake is washed with distilled water until it is neutral, and then placed in a vacuum drying oven and dried at a temperature of 80° C. for 2 h to obtain acidified carbon nanotubes;

[0033] Step S2: 0.8 g of polyvinyl pyrrolidone and 100 mL of anhydrous methanol are added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 20 min, and then 1 g of acidified carbon nanotubes is added and the mixture is stirred for reaction for 20 min, and then 50 mL of cadmium acetate solution having a molar concentration of 0.3 mol / L is added and the mixture is stirred for reaction for 1 h. After the reaction, the reaction product is adjusted to a pH of 8 with a sodium hydroxide solution having a mass fraction of 15%, and then vacuum filtered. The filter cake is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 130° C. for 2 h, and then placed in a muffle furnace and calcined at a temperature of 280° C. for 3 h, and then cooled with the furnace to obtain doped carbon nanotubes;

[0034] Step S3: 1 g of doped carbon nanotubes and 35 mL of thionyl chloride were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at 25° C. and a stirring rate of 400 r / min for 15 min, and then the mixture was heated to reflux and continued to stir for 2 h. After the reaction was completed, the reaction product was vacuum filtered, and the filter cake was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at 50° C. for 2 h to obtain chlorinated carbon nanotubes;

[0035] Step S4: 2 g of acyl chloride carbon nanotubes and 40 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 30 min at a temperature of 25° C. and an ultrasonic frequency of 40 kHz, then 0.5 g of tetraethylenepentamine was added to continue ultrasonically dispersing for 10 min, and then stirred for 8 h at a temperature of 85° C. and a stirring rate of 400 r / min under nitrogen protection. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 3 h to obtain polyamino carbon nanotubes;

[0036] Step S5: 2 g of polyamino carbon nanotubes and 120 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 30 min at a temperature of 25° C. and an ultrasonic frequency of 40 kHz, then 3 g of 4,4'-diphenylmethane diisocyanate and 0.3 g of dibutyltin dilaurate are added and ultrasonically dispersed for 10 min, and then stirred for 8 h at a temperature of 60° C. and a stirring rate of 400 r / min under nitrogen protection. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 45° C. for 10 h to obtain isocyanate-doped carbon nanotubes;

[0037] Step S6: weigh 60 parts of polymer powder, 8 parts of isocyanate-doped carbon nanotubes, 5 parts of oxidized polyethylene wax, 5 parts of polyvinyl pyrrolidone, 1.5 parts of antioxidant and 1 part of stearic acid according to weight, and set aside; the polymer powder is polypropylene powder; the antioxidant is antioxidant 1010;

[0038] Step S7: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes. Example

[0039] See also Figure 1 As shown, this embodiment is a method for preparing a conductive masterbatch based on carbon nanotubes, comprising the following steps:

[0040] Step S1: 5 g of carbon nanotubes, 105 mL of concentrated sulfuric acid with a mass fraction of 96%, and 35 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 35 min at a temperature of 28° C. and an ultrasonic frequency of 45 kHz, and then stirred for reaction for 4 h at a temperature of 88° C. and a stirring rate of 425 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filter cake is washed with distilled water until it is neutral, and then placed in a vacuum drying oven and dried at a temperature of 82° C. for 2.5 h to obtain acidified carbon nanotubes;

[0041] Step S2: 0.9 g of polyvinyl pyrrolidone and 110 mL of anhydrous methanol are added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 425 r / min for 25 min, and then 1 g of acidified carbon nanotubes is added and the stirring reaction is continued for 25 min, and then 55 mL of cadmium acetate solution with a molar concentration of 0.4 mol / L is added and the stirring reaction is continued for 1.2 h. After the reaction is completed, the reaction product is adjusted to a pH of 8.5 with a sodium hydroxide solution with a mass fraction of 18%, and then vacuum filtered, and the filter cake is washed with distilled water for 4 times, and then placed in a vacuum drying oven, dried at a temperature of 135° C. for 2.5 h, and then placed in a muffle furnace, calcined at a temperature of 290° C. for 3.5 h, and then cooled with the furnace to obtain doped carbon nanotubes;

[0042] Step S3: 1 g of doped carbon nanotubes and 38 mL of thionyl chloride were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at 28° C. and a stirring rate of 425 r / min for 18 min, and then the mixture was heated to reflux and continued to stir for 2.5 h. After the reaction was completed, the reaction product was vacuum filtered, and the filter cake was washed 4 times with distilled water, and then placed in a vacuum drying oven and dried at 55° C. for 2.5 h to obtain chlorinated carbon nanotubes;

[0043] Step S4: 2 g of acyl chloride carbon nanotubes and 42 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 35 min at a temperature of 28° C. and an ultrasonic frequency of 45 kHz, then 1.5 g of tetraethylenepentamine was added and ultrasonically dispersed for 12 min, and then stirred for 9 h at a temperature of 88° C. and a stirring rate of 425 r / min under nitrogen protection. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3.5 h to obtain polyamino carbon nanotubes;

[0044] Step S5: 2 g of polyamino carbon nanotubes and 125 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 35 min at a temperature of 28° C. and an ultrasonic frequency of 45 kHz, then 4.5 g of 4,4'-diphenylmethane diisocyanate and 0.5 g of dibutyltin dilaurate are added and ultrasonically dispersed for 12 min, and then stirred for 9 h at a temperature of 62° C. and a stirring rate of 425 r / min under nitrogen protection. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 48° C. for 12 h to obtain isocyanate-doped carbon nanotubes;

[0045] Step S6: 70 parts of polymer powder, 15 parts of isocyanate-doped carbon nanotubes, 9 parts of oxidized polyethylene wax, 9 parts of polyvinyl pyrrolidone, 2.5 parts of antioxidant and 2 parts of stearic acid are weighed in parts by weight for later use; the polymer powder is polypropylene powder; the antioxidant is antioxidant 168;

[0046] Step S7: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes. Example

[0047] See also Figure 1 As shown, this embodiment is a method for preparing a conductive masterbatch based on carbon nanotubes, comprising the following steps:

[0048] Step S1: 5 g of carbon nanotubes, 120 mL of concentrated sulfuric acid with a mass fraction of 98%, and 40 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 40 min at a temperature of 30° C. and an ultrasonic frequency of 50 kHz, and then stirred for reaction for 5 h at a temperature of 90° C. and a stirring rate of 450 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filter cake is washed with distilled water until it is neutral, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain acidified carbon nanotubes;

[0049] Step S2: 1 g of polyvinyl pyrrolidone and 120 mL of anhydrous methanol are added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 450 r / min for 30 min, and then 1 g of acidified carbon nanotubes is added and the stirring reaction is continued for 30 min, and then 60 mL of cadmium acetate solution with a molar concentration of 0.5 mol / L is added and the stirring reaction is continued for 1.5 h. After the reaction is completed, the reaction product is adjusted to a pH of 9 with a sodium hydroxide solution with a mass fraction of 20%, and then vacuum filtered, and the filter cake is washed with distilled water for 5 times, and then placed in a vacuum drying oven, dried at a temperature of 140° C. for 3 h, and then placed in a muffle furnace, calcined at a temperature of 300° C. for 4 h, and then cooled with the furnace to obtain doped carbon nanotubes;

[0050] Step S3: 1 g of doped carbon nanotubes and 40 mL of dichlorothionyl were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at 30° C. and a stirring rate of 450 r / min for 20 min, and then the mixture was heated to reflux and continued to stir for 3 h. After the reaction was completed, the reaction product was vacuum filtered, and the filter cake was washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at 60° C. for 3 h to obtain chlorinated carbon nanotubes;

[0051] Step S4: 2 g of acyl chloride carbon nanotubes and 45 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 40 min at a temperature of 30° C. and an ultrasonic frequency of 50 kHz, then 2.5 g of tetraethylenepentamine was added and ultrasonically dispersed for 15 min, and then stirred for 10 h at a temperature of 90° C. and a stirring rate of 450 r / min under nitrogen protection. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 70° C. for 4 h to obtain polyamino carbon nanotubes;

[0052] Step S5: 2 g of polyamino carbon nanotubes and 130 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 40 min at a temperature of 30° C. and an ultrasonic frequency of 50 kHz, then 6 g of 4,4'-diphenylmethane diisocyanate and 0.7 g of dibutyltin dilaurate are added and ultrasonically dispersed for 15 min, and then stirred for 10 h at a temperature of 65° C. and a stirring rate of 450 r / min under nitrogen protection. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 50° C. for 15 h to obtain isocyanate-doped carbon nanotubes;

[0053] Step S6: 80 parts of polymer powder, 22 parts of isocyanate-doped carbon nanotubes, 13 parts of oxidized polyethylene wax, 13 parts of polyvinyl pyrrolidone, 3.5 parts of antioxidant and 3 parts of stearic acid are weighed in parts by weight for later use; the polymer powder is polypropylene powder; the antioxidant is antioxidant 1076;

[0054] Step S7: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes.

[0055] Comparative Example 1:

[0056] This comparative example is a method for preparing a conductive masterbatch based on carbon nanotubes, comprising the following steps:

[0057] Step S1: weigh 80 parts of polymer powder, 22 parts of carbon nanotubes, 13 parts of oxidized polyethylene wax, 13 parts of polyvinyl pyrrolidone, 3.5 parts of antioxidant and 3 parts of stearic acid according to weight parts, and set aside; the polymer powder is polypropylene powder; the antioxidant is antioxidant 1076;

[0058] Step S2: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes.

[0059] Comparative Example 2:

[0060] This comparative example is a method for preparing a conductive masterbatch based on carbon nanotubes, comprising the following steps:

[0061] Step S1: 5 g of carbon nanotubes, 120 mL of concentrated sulfuric acid with a mass fraction of 98%, and 40 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 40 min at a temperature of 30° C. and an ultrasonic frequency of 50 kHz, and then stirred for reaction for 5 h at a temperature of 90° C. and a stirring rate of 450 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filter cake is washed with distilled water until it is neutral, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain acidified carbon nanotubes;

[0062] Step S2: 1 g of acidified carbon nanotubes and 40 mL of thionyl chloride were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 450 r / min for 20 min, then the temperature was raised to reflux and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was vacuum filtered, the filter cake was washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 3 h to obtain chlorinated carbon nanotubes;

[0063] Step S3: 2 g of acyl chloride carbon nanotubes and 45 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 40 min at a temperature of 30° C. and an ultrasonic frequency of 50 kHz, then 2.5 g of tetraethylenepentamine was added and ultrasonically dispersed for 15 min, and then stirred for 10 h at a temperature of 90° C. and a stirring rate of 450 r / min under nitrogen protection. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 70° C. for 4 h to obtain polyamino carbon nanotubes;

[0064] Step S4: 2 g of polyamino carbon nanotubes and 130 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and ultrasonically dispersed for 40 min at a temperature of 30° C. and an ultrasonic frequency of 50 kHz, then 6 g of 4,4'-diphenylmethane diisocyanate and 0.7 g of dibutyltin dilaurate are added and ultrasonically dispersed for 15 min, and then stirred for 10 h at a temperature of 65° C. and a stirring rate of 450 r / min under nitrogen protection. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 50° C. for 15 h to obtain isocyanate-doped carbon nanotubes;

[0065] Step S5: 80 parts of polymer powder, 22 parts of isocyanate-doped carbon nanotubes, 13 parts of oxidized polyethylene wax, 13 parts of polyvinyl pyrrolidone, 3.5 parts of antioxidant and 3 parts of stearic acid are weighed according to weight parts for later use; the polymer powder is polypropylene powder; the antioxidant is antioxidant 1076;

[0066] Step S6: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes.

[0067] Comparative Example 3:

[0068] This comparative example is a method for preparing a conductive masterbatch based on carbon nanotubes, comprising the following steps:

[0069] Step S1: 5 g of carbon nanotubes, 120 mL of concentrated sulfuric acid with a mass fraction of 98%, and 40 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 40 min at a temperature of 30° C. and an ultrasonic frequency of 50 kHz, and then stirred for reaction for 5 h at a temperature of 90° C. and a stirring rate of 450 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filter cake is washed with distilled water until it is neutral, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain acidified carbon nanotubes;

[0070] Step S2: 1 g of polyvinyl pyrrolidone and 120 mL of anhydrous methanol are added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 450 r / min for 30 min, and then 1 g of acidified carbon nanotubes is added and the stirring reaction is continued for 30 min, and then 60 mL of cadmium acetate solution with a molar concentration of 0.5 mol / L is added and the stirring reaction is continued for 1.5 h. After the reaction is completed, the reaction product is adjusted to a pH of 9 with a sodium hydroxide solution with a mass fraction of 20%, and then vacuum filtered, and the filter cake is washed with distilled water for 5 times, and then placed in a vacuum drying oven, dried at a temperature of 140° C. for 3 h, and then placed in a muffle furnace, calcined at a temperature of 300° C. for 4 h, and then cooled with the furnace to obtain doped carbon nanotubes;

[0071] Step S3: 80 parts of polymer powder, 22 parts of doped carbon nanotubes, 13 parts of oxidized polyethylene wax, 13 parts of polyvinyl pyrrolidone, 3.5 parts of antioxidant and 3 parts of stearic acid are weighed according to weight parts for later use; the polymer powder is polypropylene powder; the antioxidant is antioxidant 1076;

[0072] Step S4: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes.

[0073] The performance of the conductive masterbatch based on carbon nanotubes in Examples 1-3 and Comparative Examples 1-3 was tested in the following manner: the conductive masterbatch based on carbon nanotubes was added to polypropylene powder in an amount of 3-5%, and then melt-extruded through an extruder to obtain a conductive polypropylene material, and the volume resistivity of the conductive polypropylene material was tested in accordance with the requirements of GB / T1410-2006, wherein the polypropylene powder used in the examples was Shanghai Petrochemical M800E polypropylene, and the test results are shown in the following table:

[0074]

[0075] Referring to the data in the above table, according to the test results of Examples 1-3, it can be known that adding the conductive masterbatch based on carbon nanotubes in the present application can significantly improve the conductivity of the polypropylene material, and the conductive polypropylene material obtained has excellent conductive properties;

[0076] According to the comparison between Example 3 and Comparative Example 1, it can be seen that the conductivity of the unmodified carbon nanotubes is not greatly improved; according to the comparison between Comparative Example 1 and Comparative Example 2, it can be seen that the conductivity of the carbon nanotubes modified with surface organic matter is significantly improved; according to the comparison between Comparative Example 1 and Comparative Example 3, it can be seen that the conductivity of the carbon nanotubes modified by metal oxide doping is significantly improved; therefore, the conductivity improvement effect of the isocyanate-doped carbon nanotubes obtained under the synergistic effect of surface organic matter modification and metal oxide doping modification is the best.

[0077] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0078] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A conductive masterbatch based on carbon nanotubes, characterized in that: It comprises the following components in parts by weight: 60-80 parts of polymer powder, 8-22 parts of isocyanate-doped carbon nanotubes, 5-13 parts of oxidized polyethylene wax, 5-13 parts of polyvinyl pyrrolidone, 1.5-3.5 parts of antioxidant and 1-3 parts of stearic acid; the polymer powder is one of polyethylene powder, polypropylene powder, chlorinated polypropylene powder, polystyrene powder and polyamide 6 powder; the polypropylene powder is Shanghai Petrochemical M800E polypropylene; Wherein, the isocyanate-doped carbon nanotubes are prepared by the following steps: Step s1: ultrasonically dispersing carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid, and then stirring to react. After the reaction is completed, the reaction product is cooled, and then vacuum filtered, and the filter cake is washed and dried to obtain acidified carbon nanotubes; Step s2: stirring polyvinyl pyrrolidone and anhydrous methanol for reaction, then adding acidified carbon nanotubes and continuing stirring for reaction, then adding cadmium acetate solution and continuing stirring for reaction, after the reaction, adjusting the pH of the reaction product with sodium hydroxide solution, then vacuum filtering, washing, drying and calcining the filter cake to obtain doped carbon nanotubes; Step s3: stirring the doped carbon nanotubes and thionyl chloride to react, vacuum filtering the reaction product after the reaction is completed, washing and drying the filter cake to obtain chlorinated carbon nanotubes; Step s4: ultrasonically dispersing the acyl chloride carbon nanotubes and N,N-dimethylformamide, then adding tetraethylenepentamine and continuing ultrasonic dispersion, then stirring to react, cooling the reaction product after the reaction is completed, then vacuum filtering, washing and drying the filter cake to obtain polyamino carbon nanotubes; Step s5: Ultrasonic dispersion of polyamino carbon nanotubes and anhydrous toluene, then adding 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate, and continuing ultrasonic dispersion, followed by stirring for reaction. After the reaction is completed, the reaction product is cooled, and then vacuum filtered, and the filter cake is washed and dried to obtain isocyanate-doped carbon nanotubes.

2. The conductive masterbatch based on carbon nanotubes according to claim 1, characterized in that: The usage ratio of the carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step s1 is 5g:90-120mL:30-40mL.

3. The conductive masterbatch based on carbon nanotubes according to claim 1, characterized in that: The carbon nanotubes in step s1 are multi-walled carbon nanotubes with an outer diameter ranging from 40-60 nm and a length of 5-10 μm; the mass fraction of the concentrated sulfuric acid is 95-98%, and the mass fraction of the concentrated nitric acid is 68%.

4. The conductive masterbatch based on carbon nanotubes according to claim 1, characterized in that: The dosage ratio of the polyvinyl pyrrolidone, anhydrous methanol, acidified carbon nanotubes and cadmium acetate solution in step s2 is 0.8-1g:100-120mL:1g:50-60mL.

5. The conductive masterbatch based on carbon nanotubes according to claim 1, characterized in that: The molar concentration of the cadmium acetate solution in step s2 is 0.3-0.5 mol / L; the mass fraction of the sodium hydroxide solution is 15-20%.

6. The conductive masterbatch based on carbon nanotubes according to claim 1, characterized in that: The dosage ratio of the doped carbon nanotubes and thionyl chloride in step s3 is 1 g: 35-40 mL.

7. The conductive masterbatch based on carbon nanotubes according to claim 1, characterized in that: The usage ratio of the chlorinated carbon nanotubes, N,N-dimethylformamide and tetraethylenepentamine in step s4 is 2g:40-45mL:0.5-2.5g.

8. The conductive masterbatch based on carbon nanotubes according to claim 1, characterized in that: The usage ratio of the polyamino carbon nanotubes, anhydrous toluene, 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate in step s5 is 2g:120-130mL:3-6g:0.3-0.7g.

9. A method for preparing a conductive masterbatch based on carbon nanotubes, characterized in that: The following steps are involved: Step 1: Weigh 60-80 parts of polymer powder, 8-22 parts of isocyanate-doped carbon nanotubes, 5-13 parts of oxidized polyethylene wax, 5-13 parts of polyvinyl pyrrolidone, 1.5-3.5 parts of antioxidant and 1-3 parts of stearic acid according to weight parts, and set aside; Wherein, the polymer powder is one of polyethylene powder, polypropylene powder, chlorinated polypropylene powder, polystyrene powder and polyamide 6 powder; the polypropylene powder is Shanghai Petrochemical M800E polypropylene; Wherein, the isocyanate-doped carbon nanotubes are prepared by the following steps: Step s1: ultrasonically dispersing carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid, and then stirring to react. After the reaction is completed, the reaction product is cooled, and then vacuum filtered, and the filter cake is washed and dried to obtain acidified carbon nanotubes; Step s2: stirring polyvinyl pyrrolidone and anhydrous methanol for reaction, then adding acidified carbon nanotubes and continuing stirring for reaction, then adding cadmium acetate solution and continuing stirring for reaction, after the reaction, adjusting the pH of the reaction product with sodium hydroxide solution, then vacuum filtering, washing, drying and calcining the filter cake to obtain doped carbon nanotubes; Step s3: stirring the doped carbon nanotubes and thionyl chloride to react, vacuum filtering the reaction product after the reaction is completed, washing and drying the filter cake to obtain chlorinated carbon nanotubes; Step s4: ultrasonically dispersing the acyl chloride carbon nanotubes and N,N-dimethylformamide, then adding tetraethylenepentamine and continuing ultrasonic dispersion, then stirring to react, cooling the reaction product after the reaction is completed, then vacuum filtering, washing and drying the filter cake to obtain polyamino carbon nanotubes; Step s5: ultrasonically dispersing the polyamino carbon nanotubes and anhydrous toluene, then adding 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate and continuing ultrasonic dispersion, then stirring to react, cooling the reaction product after the reaction is completed, then vacuum filtering, washing and drying the filter cake to obtain isocyanate-doped carbon nanotubes; Step 2: Add polymer powder, isocyanate-doped carbon nanotubes, oxidized polyethylene wax, polyvinyl pyrrolidone, antioxidant and stearic acid into a mixer and mix evenly, then add into an extruder for melt extrusion and granulation to obtain a conductive masterbatch based on carbon nanotubes.

10. The method for preparing a conductive masterbatch based on carbon nanotubes according to claim 9, characterized in that: The antioxidant is one of antioxidant 1010 , antioxidant 168 and antioxidant 1076 .

Citation Information

Patent Citations

  • Method for preparing rare earth metal oxide and carbon nano-tube composite material of core-shell structure

    CN101264883A

  • Preparation method of carbon nano tube polyurethane composite material

    CN101870808A